Assessing resilience and adaptability in agroecological transitions - Tittonell, Pablo Adrian (Elsevier, 2020)
Guidelines are needed to support research and action on sustainable transitions towards more resilient and adaptable agroecosystems. Here I present an operationable and simple framework with theoretical underpinning to assess to what extent agroecological transitions propend to greater resilience and adaptability. Ecosystems may transition between alternative states defined by their structural and functional characteristics. Agroecological transitions are a special type of human-mediated transitions in which the various components of the agroecosystem and their interactions are reconfigured through a process of design. The concept of the complex adaptive cycle of social-ecological systems is used to propose a set of 10 criteria to monitor resilience and adaptability in agroecological transitions using a system of scores. They comprise: self-regulation, connectivity, functional diversity and redundancy, response diversity, space and time heterogeneity, building of natural capital, social self-organization, reflective learning and human capital, autonomy and local interdependency, and capitalising on local knowledge. The framework is illustrated with an example from Brazil, where national and local level socio-political drivers have supported a 30-year process of agroecological transition. Implications for policy monitoring, research for development and political discourses are discussed.